Motivations and difficulties experienced by young entrepreneurs: qualitative study - Martins, Larissa Paula (2020)
Entrepreneurship has emerged as a new form of insertion in the labor market, especially for young people. Thus, the present study aimed to understand the motivations and difficulties experienced by young people throughout the process of undertaking. The sample consisted of six young entrepreneurs, five women and one man. Semistructured interviews were applied, analyzed through content analysis. The analysis of the interviews resulted in categories related to the motivations, difficulties and characteristics of the entrepreneurs. The personal characteristics reported by the young entrepreneurs were compatible with the literature, including taking risks, communication, responsibility and creativity. The most frequent categories as motivations to undertake were prestige, influences of third and family, needs and opportunities. The difficulties highlighted were associated with initiating the project, customer support, leadership, lack of planning and physical and mental exhaustion. Through the categories listed, it is noted that effective entrepreneurship among young people requires systematic actions through public policies linked to the fields of health, education, and work.